Analisis Kesulitan Belajar Berbicara Bahasa Arab - Dwi Surya Ningsih; M Ari Wibowo; Masfiyatul Asriyah (Program Studi Pendidikan Bahasa Arab, 2022)
Arabic is the language of the qur'an, given the importance of arabic As the language of unifying people at once as spread of islam, friend Ali bin talib on his pilgrimage to kholifath has managed to make an outside contribution. Usually especially in the preservation and development of arabic, hence. The commitee (lajnah) was formed espec ially one presided over by Abu al-aswad du'ali. Not least of the Arabic sciences 'arudi, your dalta, aswat and more. The study USES qualitative descriptive lapabgan research methods. (maryaeni,2005:37) the data gathered is words,pictures,and other information because of the application of qualitative methods and all that are gathered likely to be the key to what has been studied. Qualitative analyses are those that do not use mathematical models, statistical models. and economist. Or other particular models. Studies show that difficulty analysis is leraning to speak Arabic was the first of its female subjects: an environmental factor Boarding school girls who are reluctant to talk are encouraged to proficient in Arabic and lack of motivation from the family Alone the second was to factor in the lack of the aar material in gunu terms. Highlighthing the media. Learning that hanxa is using me when students don't get it. Make up a simple setence. The position of words in the sempuma sentence. The fourth time it's a cultural socio factor. That students have not been able to understand speaking Arabic.